PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN BUOL PROPINSI SULAWESI TENGAH - Satria Harun (MM UMY, 2016)
This research was conducted in Regional Secretariat of Buol Regency, Central Sulawesi which was as the central of government. The aim of this research is to study the effect of intrinsic motivation, extrinsic motivation, and compensation to the improvement of employees’ performace in the inveronment of in Regional Secretariat of Buol Regency, Central Sulawesi. This research is expected to be reference for regional government in improving employee’s performance, especially in the environment of in Regional Secretariat of Buol Regency, Central Sulawesi. The research method used in this research was descriptive analitic method by using primary data, such as observation and questionnaires with total respondents was 74 people. The data taken was done by distributing questionnaires to all of the respondents. The instument quality test, hypothesis test, and data analysis was using multiple regression analysis and using SPSS 19.0. From the result of partial test, it is obtained the conclusion that intrinsic motivation, extrinsic motivation, and compensation of additional salary for employees have positive and significant effecr to the employees’ performance in in Regional Secretariat of Buol Regency, Central Sulawesi. From the result of simultanious test, it is obtained the conclusion that there is positive and significant effect among variables of intrinsic motivation, extrinsic motivation, and compensation to the employees’ performance in in Regional Secretariat of Buol Regency, Central Sulawesi.